Digitalization Of Baitul Maal Wa Tamwil: How Does Survival In Covid-19 Pandemic? - Muhamad Fauzi; Ahmad Darussalam (IAIN Langsa, 2022)
Covid-19 pandemic, economic activities have limitations and obstacles, including BMT trying and finding out scheme alternatives to survive in providing services. This study aims to find out the efforts of BMT to survive the Covid-19 pandemic.This study used a literature review with a descriptive approach and triangulation analysis techniques. The results showed characteristics of BMT in middle society still exist even in times of crisis. The level of public confidence in BMT providing alternative financing. Government policies have a focus on saving Islamic financial institutions. The BMT development policies prioritize liquidity, monitor DPK liquidity, and control lending or financing. This is an effort for BMT to survive in supporting liquidity, relaxation, and social safety nets. Also a task force for handling the impact of Covid-19 in the Islamic microfinance sector, guaranteeing deposits for microfinance institutions, effective supervision and reporting, and a digital business ecosystem through the human touch and technology. Thus, BMT's efforts survive by digital business application and information technology, government support, and management internalization.